Low-Frequency Noise Attenuation in a Closed Space Using Adaptive Directivity Control Sources of a Quadrupole Type - Marios GIOUVANAKIS; Christos SEVASTIADIS; George PAPANIKOLAOU (Archives of Acoustics, 2019)
A novel method of active noise control using adaptive radiation sound sources is investigated. A finite element model of a modal enclosed sound field is excited harmonically, representing a noise field in the low-frequency range. The control sources are comprised of elementary dipole sources for which the driving signals are adjusted by an optimization method. Two set-up cases of the proposed compound sources are investigated. The coupling of the control sources with the modal sound field is discussed. The simulated performance of the proposed method is compared with that of a system with distributed simple sources and the results show the effectiveness of the sources with adaptive radiation for active noise control in small enclosures.